Proceedings 24th ISUF 2017 - City and Territory in the Globalization Age 2017
DOI: 10.4995/isuf2017.2017.5706
|View full text |Cite
|
Sign up to set email alerts
|

Location-based density and diversity – adding attraction variables to space syntax

Abstract: The central variables in any urban model are distance and attraction (Wilson 2000). Space syntax research has contributed to the development of new geometric descriptions and measures of distance that have proven successful when it comes to capturing pedestrian movement. However, the description and measurement of attractions has not been central to the field. An important exception is the development of Place Syntax analysis, which concerns new methodologies and software that opens for analysis not only of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…First, this article mainly considered space syntax metrics to test the effects of street network pattern on the distribution of economic activities. Utilizing tools that can combine space syntax measurements with conventional measurements of attraction can be considered for future research (Marcus et al, 2019). Also, there are undoubtedly other morphological properties of the built environment that could have a wide range of socio-economic implications and, therefore, could be explicitly included in future work.…”
Section: Discussionmentioning
confidence: 99%
“…First, this article mainly considered space syntax metrics to test the effects of street network pattern on the distribution of economic activities. Utilizing tools that can combine space syntax measurements with conventional measurements of attraction can be considered for future research (Marcus et al, 2019). Also, there are undoubtedly other morphological properties of the built environment that could have a wide range of socio-economic implications and, therefore, could be explicitly included in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies vary in the element on which the accessibility analysis is based, such as buildings, roads, plots, etc. [125][126][127][128]. Accessibility studies vary in the scale and size of analysis, starting from a limited area of a neighborhood or urban area, moving to a city, metropolitan, or region, and even reaching the national scale [7,[15][16][17][18]117,[129][130][131][132][133].…”
Section: Accessibility Research and Physical Organization Of Space-th...mentioning
confidence: 99%
“…1 Despite these (potentially growing) theoretical shortcomings, the presumption of retailers' discrete decision making to seek locational advantages along lines of agglomeration, centrality and connectivity still holds. Over the past decades, studies continue to demonstrate the correlation between retail location and street centrality and connectivity, either through the Space Syntax definition of the ‘movement economy’ ( Hillier, 1996 ; Hillier & Hanson, 1984 ), or other methods that define the propensity of streets and street segments to attract (pedestrian) traffic, hence retail land use ( Marcus et al, 2018 ; Porta et al, 2006a , Porta et al, 2006b ; Stahle et al, 2003 ). While most of these models have been applied to cities in Europe, Asia and South America, urban scholar Andres Sevtsuk (2014) recently demonstrated that American locations with better accessibility, traffic, and clustering attract more retailers through a self-created land use dataset and street accessibility metrics.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%